ANALISIS IMPLEMENTASI MODEL PROJECT BASED LEARNING PADA PEMBELAJARAN PAI DI SMP NEGERI - Sabrina Eka Prahayuningtiyas; Ida Rindaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study analyzes the implementation of the Project-Based Learning (PjBL) model in Islamic Education (PAI) learning at State Middle Schools. With the background of the challenges of Islamic education in the modern era, which requires students to have critical thinking skills, problem-solving abilities, and creative innovation, this study aims to explore how PjBL can enhance student engagement, creativity, and learning outcomes. The research method used is a qualitative phenomenological approach to gain an in-depth understanding of the experiences of students and teachers in the implementation of PjBL. The findings show that the implementation of PjBL has proven effective in increasing student engagement and learning outcomes in the PAI subject. Through PjBL steps such as problem identification, project planning, and presenting results, students demonstrate improvements in collaboration skills and understanding of the material. Although there are challenges such as limited time and communication issues among group members, the benefits of implementing PjBL far outweigh these challenges, providing an innovative learning experience that is relevant to students' everyday lives. This study recommends the broader application of PjBL in the context of religious education to create a more active and enjoyable learning environment.